2005
DOI: 10.1007/s11577-005-0185-6
|View full text |Cite
|
Sign up to set email alerts
|

Bonus oder Bias?

Abstract: Zusammenfassung: In welchem Ausmaß ist das Lohngefälle zwischen vollzeitbeschäftigten Frauen und Männern auf Produktivitätsunterschiede zurückzuführen? Welchen Anteil hat die Diskriminierung von Arbeitnehmerinnen, und wie wirken sich betriebliche Merkmale auf die Lohnunterschiede aus? Diese Fragen untersuchen wir mit einem verbundenen Arbeitnehmer-Arbeitgeber Datensatz des Instituts für Arbeitsmarkt-und Berufsforschung für das Jahr 2000. Im Mittelpunkt steht die Frage, wie sich die Geschlechterzusammensetzung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(23 citation statements)
references
References 61 publications
1
16
1
3
Order By: Relevance
“…At present, this result contradicts other studies that focus not only on managers and clearly show stronger negative effects for women than for men (Achatz et al 2005;England et al 1988). This indicates that selection effects lead to an underestimation of this correlation for women in managerial positions.…”
Section: Managers Employed Full Time In the Private Sector: Determinacontrasting
confidence: 99%
See 2 more Smart Citations
“…At present, this result contradicts other studies that focus not only on managers and clearly show stronger negative effects for women than for men (Achatz et al 2005;England et al 1988). This indicates that selection effects lead to an underestimation of this correlation for women in managerial positions.…”
Section: Managers Employed Full Time In the Private Sector: Determinacontrasting
confidence: 99%
“…This devaluation leads to lower pay for "female" jobs; the higher the percentage of women in a specific job, the lower the pay for women as well as for men. This is indicated in the literature with the term "evaluative discrimination" (Achatz et al 2005;Peterson/Saporta 2004). 3 In addition, studies have shown that even within a specific job (i.e.…”
Section: Sociological Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Low-wage earners may be concentrated in establishments where a large share of employees are paid low wages (Bolvig 2005), so that we would expect upward mobility of individual lowwage earners to be lower if working in such an establishment. Similarly, the chances of leaving the low-wage sector may be lower for women employed in establishments with a predominantly female workforce, be it due to genderbased segregation, discrimination or just low-cost strategies in such firms (Pfeffer and Davis-Blake 1987;Achatz et al 2005). The same applies to foreigners working in establishments with a high share of foreign employees.…”
Section: Research Questions and Hypothesesmentioning
confidence: 99%
“…Vor allem für den Bereich Arbeitsmärkte gibt es inzwischen einen umfangreichen Wissensbestand (Achatz et al 2005;Bielby & Baron 1986;Hinz & Gartner 2005;Liebeskind 2004). Diese Studien zeigen im Kern, dass die Organisation von Arbeit eine entscheidende Rolle in der Herstellung und Perpetuierung sozialer Ungleichheit zwischen den Geschlechtern spielt (Castilla 2008(Castilla : 1479.…”
Section: Introductionunclassified